Mental Effects of Insomnia or How Acute Sleep Deprivation Affects our Lives - Rusu, Alexandra (New Trends in Psychology, 2023)
Insomnia is a sleep disorder manifested by difficulty falling asleep, waking up during the night or poor-quality sleep. Insomnia is a medical condition that manifests itself regardless of the degree of fatigue, in many situations people suffering from insomnia feel tired, but cannot fall asleep. Stress, anxiety and depression are among the common causes of chronic insomnia. The brain is not “asleep” during the night. He works to restore the body, and rest is essential to this process. Sleep is divided into several stages, which follow one after the other: stages 1, 2, 3, which represent non-REM sleep, and then REM sleep.